Analisis Pemanfaatan Artificial Intelligence Menggunakan Platform Chat-GPT dalam Mendukung Proses Pembelajaran Mahasiswa Universitas Bumigora - Mutiah, Mutiah; Nova Supriyedi Patty, Elyakim; Astuti Iriani, Sri (Indo-MathEdu Intellectuals Journal, 2024)
Artificial Intelligence is a system designed using technology that can make a computer system that can imitate human intellectual abilities. Chat-GPT (Generative Pre-trained Transformer) is a platform from Artificial Intelligence where it works using a conversational format. Simply put, it's like we ask a lecturer in class, but in Chat-GPT we ask an application that has been programmed to imitate human intellectual abilities so that it is able to provide answers in a short time. This study will use a quantitative approach with a descriptive method. The data of the research results was obtained through a survey by distributing questionnaires to Bumigora University students at random. Data from the study showed that most students (72%) used Chat-GPT to obtain information related to learning. By using Chat-GPT, 38.11% of students felt helped in learning and obtaining information related to learning. Chat-GPT in addition to having many benefits, also has a negative impact so there needs to be supervision for students in using this Chat-GPT platform so that academic ethical and moral values are maintained and upheld so that what students do brings benefits.